Chinese Media and United States Rebalancing Policy to Asia - Pertiwi, Sukmawani Bela (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2018)
Artikel ini bertujuan untuk melihat persepsi media di Cina terhadap kebijakan Amerika Serikat